2019
DOI: 10.1088/1742-6596/1303/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Optimization effects of design parameter on the first frequency modal of a Bridge-type compliant mechanism flexure hinge by using the Taguchi method

Abstract: The compliant mechanism always requests high displacement amplification ratio and high vibration frequency. Therefore, this paper optimized design parameters to obtain the maximum value of the first frequency modal shape using the Taguchi method. First, the model was designed by Solidworks. Second, effect design parameters on the first frequency modal shape were analyzed via ANSYS Workbench 18.0, and the final the maximum value of the first frequency modal was obtained by the Taguchi method. The simulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The Taguchi method based on grey relational analysis [20][21][22][23][24][25][26][27][28][29] was applied in this study to optimize these output characteristics.…”
Section: Grey Relational Analysis Based On Taguchi Methodsmentioning
confidence: 99%
“…The Taguchi method based on grey relational analysis [20][21][22][23][24][25][26][27][28][29] was applied in this study to optimize these output characteristics.…”
Section: Grey Relational Analysis Based On Taguchi Methodsmentioning
confidence: 99%
“…However, the deviations compared with the theoretical modeling were huge, and therefore, the optimal methods could not be approved. Thus, in this investigation, we applied TM based on grey relational analysis [18][19][20][21][22][23][24][25][26][27] to optimize these output characteristics.…”
Section: Grey Relational Analysis Based On Taguchi Methodsmentioning
confidence: 99%
“…The consistency mechanism for all types of bridges described above is the consistency mechanism for types of bridges that use flexible hinges. The presence of stiffness in the four arms of this rectangular mechanism is a serious weakness in the mechanism frequency [19,[22][23][24][25][26]. In comparison with the other bridge-type mechanisms, the distributing one is suitable for flexible multi-beam parts for increasing the resonant frequency of the mechanism, instead of notched hinges and rigid bodies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the boundary adding and structure modifying, optimization design is useful for the dynamic performance improving. Wang et al [180] studied the optimization effects on the BAM's natural frequency by using Taguchi method. The simulation results revealed that the parameters of flexure hinge significant influences the first frequency.…”
Section: Natural Frequency Of the Displacement Amplifiermentioning
confidence: 99%